Gambaran Psychological Well-Being pada Pengangguran Terdidik Ditinjau dari Jenis Kelamin, Usia, Status Pernikahan, dan Tingkat Pendidikan di Kota Padang - Alhuda Hasdi; Nurmina Nurmina (Darul Yasin Al Sys, 2026)
Although the phenomenon of educated unemployment has serious psychological implications, empirical studies on the level of psychological well-being in this group viewed from demographic characteristics remain limited. This study aimed to describe psychological well-being among educated unemployed individuals in Padang City based on gender, age, marital status, and education level. A quantitative approach with a descriptive design was employed, involving 103 educated unemployed individuals selected using purposive sampling. Data were collected using a Psychological Well-Being scale and analyzed with descriptive statistics, independent samples t-test, and one-way ANOVA. The results showed that, overall, the psychological well-being of educated unemployed individuals in Padang City was at a moderate level. There was a difference in psychological well-being based on gender, with women having higher psychological well-being than men. In addition, there were differences in psychological well-being based on marital status and education level, indicating that educated unemployed individuals who were unmarried and those with lower levels of education had higher psychological well-being, whereas age did not show a significant difference. These findings enrich the literature on psychological well-being among the educated unemployed and provide an empirical basis for designing psychosocial intervention programs that are more sensitive to demographic characteristics.